Analisis Break Even Point (BEP) dan Margin Of Safety (MOS) dalam Keputusan Perencanaan Laba pada Kedai Kopicab Bandar Lor - Nadia Nurkholisa; Ahmad Idris; Karari Budi Prasasti (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
Increasingly advanced developments and increasingly sophisticated technology have made the coffee business a promising business. This can be seen from the widespread sale of quality local coffee which is now everywhere, from roadside areas, business areas, to shopping centers. The goal of a company is definitely to make a profit. The aim of this research is to determine the minimum sales limit, sales planning, sales targets and sales safety limits using break even point (BEP) and margin of safety (MOS) analysis tools as profit planning decisions. The research method used in this research is quantitative descriptive type. The research was conducted at Kedai Kopicab which is located at Bandar Lor, Kec. Mojoroto, Kediri City, East Java. The sample in this research is all the costs incurred by Kedai Kopicab in selling Vietnam Drip products. Research data was obtained through the interview stage and financial reports held by Kedai Kopicab. The results of the research are that Kedai Kopicab wants an increase for the next three years of 10% each year and obtains a BEP value in 2024 of IDR 68,734,132, in 2025 of IDR 71,461,209, and in 2026 of IDR 74,738,514. However, even though the BEP value increases each year, the percentage obtained by Kedai Kopicab tends to decrease each year. This requires anticipating risks such as controlling costs, increasing sales, and adjusting selling prices.